Cancer patients and research during COVID-19 pandemic: A systematic review of current evidence - Moujaess, Elissar; Kourie, Hampig Raphael; Ghosn, Marwan (Critical reviews in oncology/hematology, 2020)
The novel coronavirus, also known as SARS-Cov-2 or COVID-19 has become a worldwide threat and the major healthcare concern of the year 2020. Cancer research was directly affected by the emerging of this disease. According to some Chinese studies, cancer patients are more vulnerable to COVID-19 complications. This observation led many oncologists to change their daily practice in cancer care, without solid evidence and recommendations. Moreover, the COVID-19 manifestations as well as its diagnosis are particular in this special population. In this review paper we expose the challenges of cancer management in the era of SARS-CoV-2, the epidemiological, clinical, pathological and radiological characteristics of the disease in cancer patients and its outcomes on this population. Finally, we focus on strategies that are followed in cancer management with review of national and international guidelines.